Sexual health in patients with rheumatoid arthritis and the association between physical fitness and sexual function: a cross-sectional study - Dorner, Thomas Ernst (Rheumatol Int, 2018)
The aim of this study was to examine sexual health in patients with rheumatoid arthritis (RA), and to analyse factors associated with sexual health with a focus on physical fitness. One hundred RA patients aged between 18 and 65 years were included in a cross-sectional study. Handgrip strength and knee extensor strength were measured with a dynamometer, and physical performance with the Short Physical Performance Battery (SPPB). Fifty-four patients, mean age 47.8 (SD 10.6) years, 61% female, answered a questionnaire about sexual health. Fifty-seven percent reported, at least, sometimes having difficulty with sexual intercourse (27.8% due to joint stiffness, 24.1% due to fatigue, 18.5% due to pain). Handgrip strength and knee extensor strength significantly correlated with the desire to engage in sexual intercourse, frequency of sexual contact and satisfaction with overall sex life. The SPPB total score correlated with satisfaction with overall sex life, and the SPPB repeated chair stands test with the desire to have sexual intercourse and satisfaction with overall sex life. After adjusting for age, gender, disease activity, comorbidity, co-medication and pain intensity, the repeated chair stands test remained significantly associated with the frequency of sexual contact (0.53; 0.01–1.05) and with satisfaction with overall sex life (1.39; 0.28–2.51). The results of this study show that problems with sexual health are highly prevalent in patients with RA. The ability to rise from a chair is associated with sexual function, independent of disease activity and pain intensity.